2017
DOI: 10.1080/14767058.2017.1387896
|View full text |Cite
|
Sign up to set email alerts
|

Effects and safety of delayed versus early umbilical cord clamping in newborns of HIV-infected mothers

Abstract: Objective: To investigate the effect of a 2 minutes-delayed cord clamp (DCC) versus early cord clamp (ECC) on neonate haemoglobin concentration 24 hours and 1 month after birth, and assess the safety of DCC concerning the risk of HIV infection. Design: Sixty-four mother-infant peers were enrolled. All mothers were on stable ARV therapy. Viral load, CD4 þ count and blood haemoglobin (Hb) concentrations 24 hours before delivery were collected from all mothers and their infants. Methods: All patients were enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In a randomized study of 64 mother-newborn dyads, Pogliani et al 65 compared the effect of delayed cord clamping (120 seconds) with that of early cord clamping (less than 30 seconds) in term neonates delivered by planned cesarean to mothers on stable antiretroviral therapy. Neonates who received delayed cord clamping had significantly higher mean hemoglobin concentrations at 24 hours and 1 month of age.…”
Section: Maternal Human Immunodeficiency Virus (Hiv) Infectionmentioning
confidence: 99%
“…In a randomized study of 64 mother-newborn dyads, Pogliani et al 65 compared the effect of delayed cord clamping (120 seconds) with that of early cord clamping (less than 30 seconds) in term neonates delivered by planned cesarean to mothers on stable antiretroviral therapy. Neonates who received delayed cord clamping had significantly higher mean hemoglobin concentrations at 24 hours and 1 month of age.…”
Section: Maternal Human Immunodeficiency Virus (Hiv) Infectionmentioning
confidence: 99%
“…In a study on 30 newborn infants with congenital heart disease, delayed cord clamping at 110‐130 seconds after birth showed a trend towards higher peak serum bilirubin levels than early cord clamping at less than 10 seconds . In a controlled before‐and‐after study of 64 newborn infants born to mothers with the human immunodeficiency virus, delayed cord clamping 2 minutes after birth did not result in an increased risk of neonatal jaundice when it was compared with early cord clamping within 30 seconds . Similarly, a cross‐sectional, retrospective study of 398 participants showed no increment in the prevalence of neonatal jaundice or need for phototherapy due to late clamping in newborn infants …”
Section: Discussionmentioning
confidence: 94%
“…Newborns exposed to antiretroviral therapy during pregnancy have a higher incidence of neonatal anemia (82); DCC could be effective in increasing hemoglobin concentration in the first weeks of life and reducing the need for iron prophylaxis in infancy. To our knowledge, only one study (84) compared the effect of 2 min DCC to immediate cord clamping on 64 paired mother-newborn peers. All mothers had a negative viral load (<1,000 copies/ml) and received antiretroviral therapy during pregnancy; all newborns were born by scheduled cesarean delivery.…”
Section: Methodsmentioning
confidence: 99%